Exploring School Nurse Interventions and Health and Education Outcomes: An Integrative Review. (February 2018) - Best, Nakia C.; Oppewal, Sonda; Travers, Debbie
School nurses intervene with students, parents, and school staff to advance the health and academic success of students. We conducted an integrative literature review of published research to describe the types of school nurse interventions and health and education outcome measures and to examine how school nurse interventions were linked to student outcomes. Sixty-five studies met the inclusion criteria. We used the National Association of School Nurses' Framework for 21st Century School Nursing Practice to categorize school nurse interventions and health and education outcome measures. The majority of interventions were categorized under the care coordination principle, most commonly, motivational interviewing and counseling. In 17 studies, school nurse interventions were linked to improved student outcomes. Most studies (80%) were descriptive. To advance school nursing science, researchers can build on this foundation with more rigorous research methods to evaluate the impact of school nurse interventions and activities on student health and education outcomes.